Assessment of objective ocular cyclodeviation under monocular condition and binocular condition using fundus photography. Issue 1 (24th December 2020) - Murata, Noriaki; Toda, Haruo; Amaki, Haruna; Suzuki, Kanako; Nagai, Yumi; Omiya, Yuna; Kurashima, Tomomi; Udagawa, Sachiko; Ohkubo, Shinji
Abstract : Objective: The relationship between retinal structure and function of glaucomatous eyes has attracted a great deal of research attention. However, visual field tests are conducted under monocular condition, and ophthalmic imaging was performed in patients without occlusion. We aimed to assess the objective ocular cyclodeviation between monocular occlusion and binocular conditions using fundus photography. Methods and analysis: This study included 76 healthy participants. We obtained six photos of the right eye of each patient using fundus photography. Three of the photographs were taken under monocular conditions, and the other three, under binocular conditions. We measured the optic disc margin-fovea angle (MFA) of the line connecting one point of the disc limbus and the fovea. One-way repeated analysis of variance was used to compare the angles under both conditions. We also examined the direction of ocular rotation under the binocular condition regarding the monocular condition. Results: The MFAs were 12.12°±3.83° and 12.19°±3.95° under the monocular and binocular conditions, respectively. There was no significant difference in both MFAs ( F =1.19, p=0.28). The mean cyclodeviation was 0.07°±0.80° (range: −2.40° to +2.75°). A total of 38 eyes showed excycloduction, while another 38 showed incycloduction. Conclusion: Significant cyclodeviation did not occur regardless of the existence of an occlusion. When examining the relationship between retinal structure and function, the difference in rotation angle under both conditions need not be taken into consideration if the other disease did not cause pathological cyclodeviation.